LARVICIDAL ACTIVITY OF Lawsonia inermis L. AND Senna obtusifolia L. AGAINST FOURTH INSTAR LARVAE OF Culex quinquefasciatus (SAY) (CULICIDAE: DIPTERA) (FUDMA JOURNAL OF SCIENCES, 2023)
Ethanolic leaves extract of two plants, Lawsonia inermies L. and Senna obtusifolia L. were tested on against 4th instar larvae of Culex quinquefasciatus. Three different concentration; 25000, 5000 and 75000 ppm of the plant extracts were made and tested to assess their toxicity and to determine the lethal concentrations required to kill 50% of the insect. Results show that mortality increased as the period of exposure and concentration level increased. The mortality recorded in L. inermis and S. obtusifolia at 25000 ppm was 70% and 80%, respectively, while 100% mortality was caused by 75000 ppm of each of the two plants leaf extracts. The lethal concentration causing 50% (LC50) mortality of 4th instars larvae of C. quinquefasciatus varied. These results indicated that L. inermis and S. obtusifolia extracts were toxic to immature stages of C. quinquefasciatu and could developed as a biological control agent for mosquitoes’ management
Keywords: Biocontrol, Culex quinquefasciatus, Lawsonia inermis, Senna obtusifolia, Toxicity